For structure: A critical realist critique of the use of actor-network theory in critical accounting research. Issue 3 (25th July 2019) - Modell, Sven
Abstract : Purpose: The purpose of this paper is to contrast actor-network theory (ANT) and critical realism (CR) as two contemporary approaches to critical accounting research and advance a critique centred on the neglect of social structures in the former perspective. Design/methodology/approach: This is a conceptual paper based on a critical reading of ANT inspired by CR. Findings: Although the author does not question the ability of ANT to be imbued with critical intent per se, the author is critical of its tendency to downplay the significance of pre-existing, social structures and the concomitant neglect of enduring and ubiquitous states of structural stability as an ontological possibility. This may lead to an overly optimistic view that naively valorises agency as a largely unfettered engine of emancipation. By contrast, CR offers a deeper and more nuanced ontological conception of how social structures constrain as well as enable emancipation. In contrast to the highly empiricist epistemology of ANT, it also provides an epistemological rationale for going beyond empirical descriptions of how social structures work to advance theoretically informed, explanatory critiques that are better suited for realising less easily observable opportunities for emancipation. Research limitations/implications: The paper advances the debate about how social structures should be examined in critical accounting research and the relative merits of doing so in advancing emancipatory projects. Originality/value: The paper is an attempt to contrast ANT and CR as two distinct approaches to critical accounting research and thus extends the debate about what such research is and could be.